Supercontinuum generation in the black light region by pumping at 355 nm a silica photonic crystal fiber - Sylvestre, Thibaut; Ragueh, A. R.; Lee, M. W.; Stiller, Birgit; Fanjoux, G.; Barviau, Benoit; Mussot, Arnaud; Kudlinski, Alexandre (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
We have developed a fibre-based source of "black light", a source that emits broadband ultraviolet radiation but only small amounts of visible light and no infrared light. We made this source by pumping a specially designed silica photonic crystal fibre with 355 nm light pulses from a Q-switched frequency-tripled Nd:YAG laser. Four-wave mixing and cascaded Raman generation combine in the fibre to provide a broadband continuum output that spans from around 350 nm to 390-470 nm, with the exact spectral width dependent on the pump power. We discuss the main limitations in terms of bandwidth and power due to temporal walk-off, fiber attenuation and solarization and we suggest simple solutions for further progress. This broadband black-light source could be useful for performing gas absorption spectroscopy or exciting various fluorescent proteins used in biological studies. © 2012 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
CRIS-Team Scopus Importer:2021-06-29
Keywords: Four-wave mixing; Photonic crystal fibers; Stimulated Raman scattering; Supercontinuum generation